Urban Farming for Food Security Enhancement in Tunjungsekar Using a 3D-FDM Selective Compliance Articulated Robot Arm - Maulana, Eka; Nabawi, Naufal; Nusantoro, Goegoes Dwi; Muchamad Ali Safa'at (Fakultas Teknik, Universitas Brawijaya, 2026)
Indonesia faces significant food security challenges driven by rapid population growth, urbanization, and agricultural land conversion. Malang City, with a dense population and ranked 42nd in the national Food Security Index (IKP), requires innovative approaches to strengthen urban agriculture. This community service program, conducted in Tunjungsekar Village, Lowokwaru District, introduced a modern urban farming system as a practical solution. The implementation included the construction of an ergonomic greenhouse using galvanum hollow and esther steel frames, along with the deployment of a 3D-FDM-based SCARA robot integrated with kinematics, PID control, and the Internet of Things (IoT) for automated irrigation and plant care. The results demonstrated a 40% increase in community participation from the initial discussion phase to installation, reflecting growing awareness and enthusiasm toward urban farming practices. This innovation not only improved efficiency and productivity but also contributed directly to the enhancement of Malang City’s Food Security Index. Furthermore, the robotic urban farming model is expected to be replicated in other urban areas as a strategic effort to support national food self-sufficiency programs and the achievement of the Sustainable Development Goals (SDGs).